2017
DOI: 10.1016/j.ymthe.2016.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Antisense Reduction of Mutant COMP Reduces Growth Plate Chondrocyte Pathology

Abstract: Mutations in cartilage oligomeric matrix protein cause pseudoachondroplasia, a severe disproportionate short stature disorder. Mutant cartilage oligomeric matrix protein produces massive intracellular retention of cartilage oligomeric matrix protein, stimulating ER and oxidative stresses and inflammation, culminating in post-natal loss of growth plate chondrocytes, which compromises linear bone growth. Treatments for pseudoachondroplasia are limited because cartilage is relatively avascular and considered inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Since structural mutations in collagen I in OI (and other ECM proteins in other ECMopathies) can exert such strong dominant gain‐of‐function effects, a goal of gene targeting approaches is complete, or near‐complete, mutant gene expression knock‐down. Antisense oligonucleotides, ribozymes, and small interfering RNAs have shown experimental efficacy for both COL1A1 (Lindahl et al, ; Rousseau et al, ) and COMP (Posey et al, ) mutations in vitro , and in the case of COMP mutations antisense delivery reduces the severity of the growth plate cartilage pathology in a pseudoachondroplasia mouse model (Posey et al, ). However, there are still significant obstacles to clinical delivery, along with uncertainties about possible off‐target effects.…”
Section: Therapeutic Approaches—targeting the Upr?mentioning
confidence: 99%
“…Since structural mutations in collagen I in OI (and other ECM proteins in other ECMopathies) can exert such strong dominant gain‐of‐function effects, a goal of gene targeting approaches is complete, or near‐complete, mutant gene expression knock‐down. Antisense oligonucleotides, ribozymes, and small interfering RNAs have shown experimental efficacy for both COL1A1 (Lindahl et al, ; Rousseau et al, ) and COMP (Posey et al, ) mutations in vitro , and in the case of COMP mutations antisense delivery reduces the severity of the growth plate cartilage pathology in a pseudoachondroplasia mouse model (Posey et al, ). However, there are still significant obstacles to clinical delivery, along with uncertainties about possible off‐target effects.…”
Section: Therapeutic Approaches—targeting the Upr?mentioning
confidence: 99%
“…In a second approach, we tested whether systemic administration would deliver COMP targeted antisense oligonucleotides (ASO) to growth plate chondrocytes and decrease MT-COMP growth plate chondrocyte pathology [96]. We found that ASO1 was successfully delivered reducing steady-state levels of cartilage oligomeric matrix protein mRNA dampening intracellular retention of MT-COMP.…”
Section: Towards Understanding the Psach Chondrocyte Pathologymentioning
confidence: 99%
“…We found that ASO1 was successfully delivered reducing steady-state levels of cartilage oligomeric matrix protein mRNA dampening intracellular retention of MT-COMP. Interestingly, although ASO1 was designed against human COMP, mutant human COMP mRNA was reduced 38% and wild-type mouse COMP mRNA was reduced 60% [96]. Reduction in COMP retention in chondrocytes, led to a reduction of inflammatory markers, interleukin-16 (IL-16) and chitinase-like 3 (Chil3/YM1 a macrophage protein), the number of TUNEL positive chondrocytes, and a partial restoration of DNA proliferation [96].…”
Section: Towards Understanding the Psach Chondrocyte Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…one mutant subunit causing a dominant negative effect that results in the protein being trapped in the ER. 39 Ultimately, the rough ER of affected chondrocytes enlarge, filling the cytoplasmic space and being cytotoxic to growth plate chondrocytes. 2,20,32,34 Previously, a doxycycline-inducible mouse model that expresses MT-COMP (D469del) in growth plate chondrocytes, and that recapitulates the clinical phenotype and chondrocyte pathology of PSACH, was generated, validated, and used to identify the pathologic mechanisms.…”
mentioning
confidence: 99%